METHODOLOGY AND RESULTS OF THE MAIN TECHNICAL OF PARAMETERS OF THE MANEUVERABLE UNMANNED AERIAL VEHICLE JUSTIFICATION - M. A. Kiselev (Научный вестник МГТУ ГА)
The recent experience of creating an unmanned combat aerial vehicle indicates that the main problems do not concern the development of an unmanned fighter as an aerial vehicle. The greatest challenge lies in creating the algorithms, data sensors, control hardware, communications hardware, etc. necessary for utilization of an unmanned aerial vehicle (UAV). In this context it is important to highlight the problem of replacing the pilot as a sensor and a flight operator on board of the UAV. This problem can be partially solved by introducing remote control, but there are some flight stages where it can only be executed under a fully independent control and data support due to various reasons, such as tight time, short duration, lack of robust communication, etc. These stages include combat deployment (surface attack or air attack) which make the highest demands on the fighter's design, that is why the promising UAV are currently considered to be "as autonomous as possible". It is obvious that the efficiency of an autonomous UAV will be determined mostly by the effectiveness of its automated control algorithms, and this dependence will increase together with the level of UAV autonomy. On the other hand, the optimal control algorithms can only be synthesized based on the control object characteristics. It means the development of UAV external design and the synthesis of its control algorithms should occur simultaneously and interdependently. This article presents the content and gives an example of the use of the method of maneuverable UAV external design, the distinctive feature of which lies in the interdependent processes of UAV external design developing and the synthesizing of its automated control algorithms.